A proposal of new diagnostic pathway for fatal familial insomnia. Issue 6 (18th November 2013) - Krasnianski, A; Sanchez Juan, P; Ponto, Claudia; Bartl, M; Heinemann, U; Varges, D; Schulz-Schaeffer, W J; Kretzschmar, H A; Zerr, I
Abstract : Background: In absence of a positive family history, the diagnosis of fatal familial insomnia (FFI) might be difficult because of atypical clinical features and low sensitivity of diagnostic tests. FFI patients usually do not fulfil the established classification criteria for Creutzfeldt–Jakob disease (CJD); therefore, a prion disease is not always suspected. Objective: To propose an update of diagnostic pathway for the identification of patients for the analysis of D178-M129 mutation. Design and methods: Data on 41 German FFI patients were analysed. Clinical symptoms and signs, MRI, PET, SPECT, polysomnography, EEG and cerebrospinal fluid biomarkers were studied. Results: An algorithm was developed which correctly identified at least 81% of patients with the FFI diagnosis during early disease stages. It is based on the detection of organic sleep disturbances, either verified clinically or by a polysomnography, and a combination of vegetative and focal neurological signs and symptoms. Specificity of the approach was tested on three cohorts of patients (MM1 sporadic CJD patients, non-selected sporadic CJD and other neurodegenerative diseases). Conclusions: The proposed scheme may help to improve the clinical diagnosis of FFI. As the sensitivity of all diagnostic tests investigated but polysomnography is low in FFI, detailed clinical investigation is of special importance.